Water Pump Management Using Photovoltaic Plates in Santa Fe - Amazonas Community - Sabino da Silva, Antônio Jackson; da Silva Oliveira, Livia; Barbosa de Alencar, David; Estanislau Sanches, Antônio (International Journal for Innovation Education and Research, 2019)
Electricity in today’s world is one of the biggest concerns. Through clean sources, photovoltaic systems emerge as an alternative to this kind of problem.This work proposes the development of a photovoltaic system that will be applied to water pumping using a pump. Through the presented data, it will be possible to analyze if the photovoltaic energy is reliable and to propose solutions to the problem of residential water supply in the communities that do not have access to the electricity grid.